2015
DOI: 10.7251/bii1502083g
|View full text |Cite
|
Sign up to set email alerts
|

Kvantitativna analiza magnocelularnog dijela nucleus ruber-a

Abstract: Kratak sadržajUvod. Nucleus ruber zauzima centralni dio retikularne formacije srednjeg mozga, od donjeg kraja gornjih kvržica srednjeg mozga do ventralnog talamusa. Vaskularizuju ga grane P 1 i P 2 segmenta arteriae cerebri posterior, arteriae communicans posterior i arteriae choroidea anterior. Ciljevi rada su kvantitativna analiza neurona i vaskularne mreže magnocelularnog dijela nucleus ruber-a, kao i ispitivanje uticaja starenja na parametre kvantitativne analize.Metode. Deset srednjih mozgova odraslih lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…15 The volume density of the blood vessels of the magnocellular part of the nucleus ruber is 0.014 mm 0 , the surface density is 4.19 mm -1 , while the length density is 90.82 mm -2 . 16 All examined parameters of the vascular network of the SC were lower than the vascular density of the principal oculomotor nucleus and higher than the magnocellular part of the nucleus ruber. Based on these values, it is noticed that the blood vessels of the principal oculomotor nucleus are larger and more convoluted in comparison with the blood vessels of the SC and the magnocellular part of the nucleus ruber, which predisposes the principal oculomotor nucleus to a more frequent vascular occlusion.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…15 The volume density of the blood vessels of the magnocellular part of the nucleus ruber is 0.014 mm 0 , the surface density is 4.19 mm -1 , while the length density is 90.82 mm -2 . 16 All examined parameters of the vascular network of the SC were lower than the vascular density of the principal oculomotor nucleus and higher than the magnocellular part of the nucleus ruber. Based on these values, it is noticed that the blood vessels of the principal oculomotor nucleus are larger and more convoluted in comparison with the blood vessels of the SC and the magnocellular part of the nucleus ruber, which predisposes the principal oculomotor nucleus to a more frequent vascular occlusion.…”
Section: Resultsmentioning
confidence: 87%
“…Based on these values, it is noticed that the blood vessels of the principal oculomotor nucleus are larger and more convoluted in comparison with the blood vessels of the SC and the magnocellular part of the nucleus ruber, which predisposes the principal oculomotor nucleus to a more frequent vascular occlusion. 17,18 With ageing, no changes in the studied stereological parameters of the blood vessels of the principal oculomotor nucleus and the magnocellular part of the nucleus ruber were observed, 19,16 while the blood vessels of Discussion the SC show a decrease in the length density with age, which means that their tortuosity decreases, which was not seen in other structures at the same transversal level.…”
Section: Resultsmentioning
confidence: 94%
“…40 Our previous studies of neurons in the magnocellular part of the red nucleus have shown the reduction of the quantitative parameters with age, but the decrease did not reach statistical significance. 42 We mention this because of the proximity of red nucleus and SN at the same midbrain level, and there is a joint functional activity in the extrapyramidal system. This is confirmed by Lambert and associates, who showed the reduction in the number of neurons, gliosis and increased levels of iron with aging in SN and red nucleus.…”
Section: Discussionmentioning
confidence: 98%